Flexible service resource allocation model based on the maximization of social welfare - Wei YAN; Xiao-rong ZHU; Shou-ning CHEN; Shi-xiang SHAO (Tongxin xuebao)
The application of economic principles in the management of the radio resource was studied. The allocation of radio resource was considered as a production-consumption model considering service, user, resource domain and taking the principle of the user fairness into account. Radio resource was allocated to different types of QoS users in different ways, and the model of resource allocation based on the maximization of social welfare was established. The scheduling algorithm based on flexible service was used to optimize the proposed model with considering the utility of the users, the benefits of the network and the incomes of the operators, so that the flexible service resource allocation based on the maximization of social welfare was established. The simulation results show the excellences of the proposed algorithm.